1962
DOI: 10.1017/s0022172400020477
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and significance of Phase 1 complement-fixing antibody in Q fever

Abstract: 1. An attempt has been made to follow up a consecutive series of seventy-two patients for the presence of Phase 1 C.F. antibody approximately 2 years or more after the acute illness. Fifty-one of the series were tested.2. Fifteen of the fifty-one patients had detectable amounts of antibody, generally in low titre.3. The presence of Phase 1 antibody correlated well, in older age-groups, with the duration of convalescence following the acute illness. There was no correlation with the duration of fever.4. All cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In 1962, Powell and Stallman found that detection of IgG I was associated with protracted convalescence from Q fever in the elderly. However, the authors stated that the presence of phase I antibodies was an indication of "past persistent infection" but that it was not necessarily proof of present persistent infection in the absence of clinical signs (382). One year later, the WHO study group on rickettsial diseases established a serological cutoff for phase I antibody titers at 1:200 for the diagnosis of "chronic Q fever" (383).…”
Section: Clinical Aspects Chronic Q Fever: From Historical Backgroundmentioning
confidence: 99%
“…In 1962, Powell and Stallman found that detection of IgG I was associated with protracted convalescence from Q fever in the elderly. However, the authors stated that the presence of phase I antibodies was an indication of "past persistent infection" but that it was not necessarily proof of present persistent infection in the absence of clinical signs (382). One year later, the WHO study group on rickettsial diseases established a serological cutoff for phase I antibody titers at 1:200 for the diagnosis of "chronic Q fever" (383).…”
Section: Clinical Aspects Chronic Q Fever: From Historical Backgroundmentioning
confidence: 99%
“…The inability of the workers to recall symptoms which could be attributed to a previous attack of Q fever is possibly explained by subclinical infections or because Q fever may pass unrecognized and be regarded as an attack of influenza or bronchitis. The presence of complement-fixing antibody to phase 1 antigen in two employees may indicate past persistent infection (Powell and Stallman, 1962).…”
Section: The Incidence Of Antibodies In Blood Donors In Great Britainmentioning
confidence: 99%
“…Of diagnostic importance is the production of antibodies against C. burnetii antigens in a temporal manner, with phase II antibodies appearing early and phase I antibodies appearing somewhat later in the course of infection (7,14,19,25,34). Presence of phase I antibodies correlates well in older age groups with the duration of convalescence after the acute illness (34).…”
mentioning
confidence: 99%